Effectiveness of Recombinant Human Growth Hormone for Pharyngocutaneous Fistula Closure - BİNNETOĞLU, ADEM; YUMUŞAKHUYLU, ALİ CEMAL (KOREAN SOC OTORHINOLARYNGOL, 2015)
Objectives. In laryngeal cancer, which comprises 25% of head and neck cancer, chemotherapy has come into prominence with the increase in organ-protective treatments. With such treatment, salvage surgery has increased following recurrence; the incidence of pharyngocutaneous fistula has also increased in both respiratory and digestive system surgery We investigated the effects of recombinant human growth hormone on pharyngocutaneous fistula closure in Sprague-Dawley rats, based on an increase in amino acid uptake and protein synthesis for wound healing, an increase in mitogenesis, and enhancement of collagen formation by recombinant human growth hormone. Methods. This study was experimental animal study. Forty Sprague-Dawley rats were separated into two groups, and pharyngoesophagotomy was perfouned. The pharyngoesophagotomy was sutured with vicryl in both groups. Rats in group 1 (control group) received no treatment, while those in group 2 were administered a subcutaneous injection of recombinant human growth hormone daily. On day 14, the pharynx, larynx, and upper oesophagus were excised and examined microscopically. Results. Pharyngocutaneous fistula exhibited better closure macroscopically in the recombinant human growth hormone group. There was a significant difference in collagen formation and epithelisation in the recombinant human growth hormone group compared to the control group. Conclusion. This study is believed to be the first in which the effect of recombinant human growth hormone on pharyngocutaneous fistula closure was evaluated, and the findings suggest the potential of use of growth hormone for treatment of pharyngocutaneous fistula.
Keywords: Pharyngocutaneous Fistula; Recombinant Human Growth Hormone; Postoperative Laryngectomy Complications; LARYNGECTOMY; RATS; CHILDREN; CANCER; BONE